2020
DOI: 10.1016/j.asmr.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Analysis at Two Time Points in Three High-Impact Orthopaedic Sports Medicine Journals

Abstract: Purpose: To determine how well the orthopaedic sports medicine literature reported sex-specific analysis (SSA) in 2011 and 2016. Methods: The 3 highest-impact orthopaedic sports medicine subspecialty journals (American Journal of Sports Medicine; Arthroscopy; and Knee Surgery, Sports Traumatology, Arthroscopy) were selected for review. Two independent investigators reviewed all journal issues published during 2 different calendar years (2011 and 2016). All randomized controlled, prospective and retrospective g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…24 Despite the push for improving the inclusion of females as research subjects, only a fraction of orthopaedic studies—roughly one-third—have done sex-specific analysis. 23,25,26 The lack of sex-specific reporting is of particular concern because when data are analyzed as a function of the patient's sex, a notable difference in outcomes is detected as often as 39% of the time. 26…”
Section: History Of Reporting Effect Of Patient Gender or Sex On Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Despite the push for improving the inclusion of females as research subjects, only a fraction of orthopaedic studies—roughly one-third—have done sex-specific analysis. 23,25,26 The lack of sex-specific reporting is of particular concern because when data are analyzed as a function of the patient's sex, a notable difference in outcomes is detected as often as 39% of the time. 26…”
Section: History Of Reporting Effect Of Patient Gender or Sex On Resultsmentioning
confidence: 99%
“…23,25,26 The lack of sex-specific reporting is of particular concern because when data are analyzed as a function of the patient's sex, a notable difference in outcomes is detected as often as 39% of the time. 26…”
Section: History Of Reporting Effect Of Patient Gender or Sex On Resultsmentioning
confidence: 99%
“…Similarly, a study by Gianakos et al. 8 found that 30.5% of studies in 3 high-impact orthopaedic sports medicine subspecialty journals included SSA. Furthermore, another study by Gianakos et al.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, Hettrich et al 6 found that there was an increase in SSA reporting in high-impact orthopaedic journals from 2000 to 2010, but overall, fewer than one-third of studies included SSA. Similarly, a study by Gianakos et al 8 found that 30.5% of studies in 3 high-impact orthopaedic sports medicine subspecialty journals included SSA. Furthermore, another study by Gianakos et al 9 evaluated all articles published in 6 leading orthopaedic journals in 2016.…”
mentioning
confidence: 91%
“…There is still a relative disparity of knowledge about women's sports injuries. [13][14] In their article "Sex Differences in Posterior Cruciate Ligament Injuries," Drs. Oganesyan, Anderson, Simeone, Chang and Tanaka continue that pursuit of narrowing the information gap by evaluating patterns of injury in the posterior cruciate ligament (PCL) injuries on MRI.…”
mentioning
confidence: 99%